Activity Types Selection in Kindergarten Outdoor Education - Hsin-Ying, Liu; Yao-Hsu, Tsai; Cheng-I, Hou; Chih-Yao, Lo (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Preschool education develops from focus on physical cultivation in traditional agricultural society to professional education in professional institutions such as kindergartens. In recent years, it emphasizes multiple development and interactive instruction. By field perception, it constructs multi-dimensional and multi-level instruction. Outdoor education is gradually valued and operated. Through personal experience and interactive learning, it explores the meanings of natural environment and culture, learns responsibility and cognition, enhances application and thinking capacity, cultivates the correct concept of environmental protection, social justice and life recognition in order to accomplish the goals of environmental education and diverse development and be different from rigid and limited knowledge and learning of traditional books in schools. This study focused on selection of activity types in kindergarten outdoor education. Based on literature review, this study designed semi-open-ended questionnaire to collect expert opinions, and used expert questionnaire of Modified Delphi Method for individual interview. According to expert opinions, the important factors were identified. Finally, AHP questionnaire was designed. This study discussed the concerns and preferences of kindergartens in Miaoli County regarding outdoor education in research process. The results revealed the expectation of residents in Miaoli County, educational experts and scholars and governmental personnel toward talent cultivation.Â 